Integrated View of Population Genetics - Trindade Maia, Rafael; de Araújo Campos, Magnólia (IntechOpen, 2019)
Population genetics is the basis of evolutionary studies, and has been widely used in several researches. This recent field of science has important applications for the management of populations (natural and domesticated), as well as for evolutionary studies of the various factors that affect gene frequencies over time and spatial distribution.In this work, presented in three sections (Population and Quantitative Genetics, Genetic Diversity in Crop Management, Population Genetics for Conservation Studies), the reader will find cutting-edge information in carefully selected and revised works.This book is intended for all researchers, academics, and students who are interested in the intriguing area of population genetics.